Construction of inorganic–organic 2D/2D WO3/g-C3N4 nanosheet arrays toward efficient photoelectrochemical splitting of natural seawater. Issue 15 (29th March 2016) - Li, Yuangang; Wei, Xiaoliang; Yan, Xiangyang; Cai, Jiangtao; Zhou, Anning; Yang, Mengru; Liu, Kaiqiang
Abstract : Inorganic–organic 2D/2D WO3 /g-C3 N4 nanosheet arrays are fabricated and proved to be an efficient and stable photoanode for photoelectrochemical splitting of natural seawater. Abstract : Hydrogen production from seawater and solar energy based on photoelectrochemical cells is extremely attractive due to earth-abundance of seawater and solar radiation. Herein, we report the successful fabrication of novel inorganic–organic 2D/2D WO3 /g-C3 N4 nanosheet arrays (WO3 /g-C3 N4 NSAs) grown on a FTO substrate via a facile hydrothermal growth and deposition-annealing process, and their application in natural seawater splitting. The results indicate that the WO3 /g-C3 N4 NSAs exhibit a photocurrent density of 0.73 mA cm −2 at 1.23 V versus RHE under AM 1.5G (100 mW cm −2 ) illumination, which is 2-fold higher than that of WO3 NSAs. More importantly, the WO3 /g-C3 N4 NSA photoanode is quite stable during seawater splitting and the photocurrent density does not substantially decrease after continuous illumination for 3600 s. The remarkably enhanced performance originates primarily from the formation of the WO3 /g-C3 N4 heterojunction between WO3 and g-C3 N4 nanosheets, which accelerates charge transfer and separation, and prolongs the lifetime of electrons as demonstrated by EIS and Mott–Schottky analyses. Finally, a possible mechanism for the improved performance was proposed and discussed.